Salt stress induced changes in protein profile of tolerant (Kh 65) and sensitive (HD 2009) wheat genotypes - Ram, Sewa; Rana, Veenti; Sharma, Indu (Journal of Cereal Research, 2014)
In addition to drought and extreme temperatures, soil salinityrepresents a growing threat to wheat crop productivity. Therefore,understanding molecular mechanism involved in salinity stress canhelp in developing salt tolerant cultivars. In this investigation acomparative proteome analysis using 2-D electrophoresis was carriedout between salt sensitive variety HD 2009 and salt tolerant varietyKh 65 to identify differentially expressed protein subunits. Salttreatment (12 ECe) was given to 2 week old seedlings under controlledconditions in Growth Chamber. Chemical and physical parameterswere recorded after 72 hrs of salt treatment. 2D- electrophoresis ofproteins extracts from root tissues was conducted under control andtreated conditions. There was reduction in root biomass by 32 and 56per cent in Kh 65 and HD 2009, respectively. A total of more than200 spots were identified on the gel among them 60 spots showeddifferential expression in both the cultivars in combination. Amongthem, seventeen spots (3, 6, 8, 9, 11, 12, 14, 15, 21, 23, 25, 27, 30, 33,30, 35 and 36) were up-regulated and while fifteen (2, 4, 5, 7, 13, 16,17, 18, 20, 22, 26, 31, 37, 38 and 39) down-regulated in Kh65. Whereasonly five spots (4, 35, 36, 58, 59) were up-regulated in HD 2009 andtwenty one (1, 2, 3, 5, 9, 26, 37, 38, 40, 42, 43, 44, 45, 46, 47, 49, 52,53, 54, 56, and 60)down-regulated. These differentially expressedspots can be isolated and sequenced for identifying protein subunitsaffected by salt stress.